Enhanced X-ray emission from candidate Lyman continuum emitting galaxies. Issue 3 (6th June 2019) - Bluem, J; Kaaret, P; Prestwich, A; Brorby, M
ABSTRACT: X-ray binaries may have helped reionize the early Universe by enabling Lyman continuum escape. We analysed a set of eight local galaxies that are potential Lyman leaking galaxies, identified by a blue colour and weak emission lines, using Chandra X-ray observations. Five of the galaxies feature X-ray sources, while three galaxies are not significantly detected in X-rays. X-ray luminosities were found for the galaxies and X-ray sources. Four of the galaxies have elevated X-ray luminosity versus what would be expected based on star formation rate and metallicity. The presence of detected X-ray sources within the galaxies is found to correlate with the ratio of the star formation rate estimated from the near-ultraviolet flux to that estimated from the infrared. This implies reduced obscuration due to dust in the galaxies with X-ray sources. These results support the idea that X-ray binaries may be an important part of the process of reionziation.